Foreign exchange practices of National Bank Limited Gulshan Corporate Branch - MOUMITA, SHAYEDA AFSAR (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.